A Predictive Investment Scheme for Dhaka Stock Exchange - Kamal, A. H. M.; Abdullah, Md. Kaysar (Digital Technologies Research and Applications, 2022)
Stock market plays a vital role in industrial development of a country. People invest money to make profit from market. Inexperience investors cannot yield profit due to their weak predictions. This research tries to understand the nature of those investors and their demands. Most investors first analyze the prospect of companies based on rate of up-down in prices of share, given bonus, companies’ goodwill, temptation by others, etc.. This research presents a good prediction methodology for the stock market investors and thus, will help them to achieve a profit. It will improve the stability of a market.